USING POWERPOINT PRESENTATIONS IN ENGLISH LESSONS - Khusanova, Indira (Журнал иностранных языков и лингвистики, 2023)
Our article looks at the effectiveness of using PowerPoint presentations in English classes. When explaining and deepening grammatical material, they give priority to presentations, since the step-by-step presentation of the material and, above all, the descriptive character (diagrams, tables) make it easier for them to absorb information.